Y-index of Different Corona Products of Graphs - Agnes, V. Sheeba; Kannadasan, C. (Communications in Mathematics and Applications, 2023)
For a molecular graph \(G\), the \(Y\)-index is defined as the sum of fourth degree of all vertices of the graph. Among different products, corona product of two graphs is one of the most important. In this paper, we explore the explicit expressions of \(Y\)-index of different types of corona product of graphs.